Bacterial Meningitis in Patients using Immunosuppressive Medication: a Population-based Prospective Nationwide Study - van Veen, Kiril E. B. (J Neuroimmune Pharmacol, 2016)
We studied occurrence, presentation, disease course, effect of adjunctive dexamethasone, and prognosis of bacterial meningitis in patients using immunosuppressive medication. Patients were selected from our nationwide, prospective cohort on community-acquired bacterial meningitis performed from March 1, 2006 through October 31, 2014. Eighty-seven of 1447 episodes (6 %) of bacterial meningitis occurred in patients using immunosuppressive medication, and consisted of corticosteroids in 82 %. Patients with bacterial meningitis using immunosuppressive medication were less likely to present with headache (P = 0.02) or neck stiffness (P = 0.005), as compared those not on immunosuppressive medication. In 46 % of episodes CSF leukocyte count was below 1000/mm(3). CSF cultures revealed S. pneumoniae in 41 % and L. monocytogenes in 40 % of episodes. Outcome was unfavorable in 39 of 87 episodes (45 %) and death occurred in 22 of 87 episodes (25 %). Adjunctive dexamethasone was administered in 52 of 87 (60 %) episodes, and mortality tended to be lower in those on adjunctive dexamethasone therapy as compared to those without dexamethasone therapy (10 of 52 [19 %] vs 12 of 35 [34 %], P = 0.14). We conclude that bacterial meningitis in patients using immunosuppressive medication is likely to present with atypical clinical and laboratory features, and is often caused by atypical bacteria, mainly L. monocytogenes. Adjunctive dexamethasone is widely prescribed in these patients and was not associated with harm in this study.